Legal Protection Towards Workers With Disabilities In Bali Province - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini (Fakultas Hukum Universitas Lampung, 2021)
Protection for workers, especially workers with disabilities, where the government recognises the safety and existence of workers with disabilities. Labour is part of the subject of employment which is considered able to do a job to produce goods or services to meet the needs of themselves and the community. When referring to the existing legislation, workers with disabilities' position in obtaining employment and the legal protection of the rights of workers with disabilities is the same as that of a non-disabled person. The Government of Indonesia has committed and seriousness to respect, protect, and fulfil the rights of persons with disabilities, which is ultimately expected to improve the welfare of people with disabilities. Therefore, the government is obliged to realise the rights contained in the convention through adjustment of legislation, including ensuring the persons with disabilities rights in all aspects of life. This article would like to find out the implementation of the legal protection towards the disabilities workers in Indonesia and what forms of legal protection should be implemented. Therefore, this article will use research methods of legal normative and with statute approach, conceptual approach, and comparative approach. The researchers found that the legal protection towards disabilities is sufficiently proven by the regulation and policies that are applicable.